Ice and the Ecothriller: Popular Representations of Antarctica in the Anthropocene - Elizabeth Leane (2019)
In The Great Derangement: Climate Change and the Unthinkable , Amitav Ghosh (2016, p. 8) identifies a ‘[broad] imaginative and cultural failure that lies at the heart of the climate crisis’. Ghosh is concerned specifically with ‘serious’ or ‘literary’ fiction, which, he argues, foregrounds the everyday over the improbable, exceptional or catastrophic event. Novels featuring such events, he observes, are automatically banished to the ‘generic outhouses’ of fantasy, horror and science fiction (p. 24). Ghosh does not mention one of the biggest selling of all popular genres: the thriller. However, this genre – particularly in its geopolitical form – trades on the improbable, with the hero routinely performing spectacular feats of daring to prevent imminent nuclear war, global epidemic outbreak or, more recently, environmental catastrophe. Ghosh is not alone in overlooking the thriller: literary critics, even those interested in genre fiction, also largely ignore it. In her introduction to Popular Fiction and Spatiality , Lisa Fletcher (2016, p. 4) notes that this popular genre has produced less criticism than any other. This is even more true of the thriller’s environmentally inflected subgenre, the ecothriller. While the term (sometimes hyphenated or separated into two words) is current in popular discourse – a Google search produces more than a hundred thousand hits – it barely registers in academia. Only two of more than two million entries in the Modern Languages Association bibliography mention ‘eco(-)thriller’; none includes the term ‘environmental thriller’; only nine can be found from a general search on the combined terms ‘thriller’ and ‘environment(al)’. Richard Kerridge’s short article ‘Ecothrillers: environmental cliffhangers’, published in 2000, remains one of very few critical efforts to directly address the subgenre as a whole. And yet, the thriller, with its tendency to operate across large, often global, spaces, its willingness to deal with the improbable and its emphasis on action, is a ...